2020
DOI: 10.1186/s12888-020-02804-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the severity of psychological distress among four groups of an Iranian population regarding COVID-19 pandemic

Abstract: Background: Coronavirus disease 2019 (COVID-19) pandemic has caused serious psychological problems, including panic attack, anxiety, stress, and depression. The main objective of this study was to measure the prevalence and compare the severity of this psychological distress among four groups of an Iranian population. Method: In a cross-sectional survey, the mental health status of four groups of an Iranian society including community population, patients with COVID-19, medical staff, and medical students were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
111
3
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 37 publications
9
111
3
7
Order By: Relevance
“…As a result of the increase in the time spend on social media, the students have become more exposed to read, heard, or see news related to the COVID-19 and therefore they were psychologically affected. Similar findings were previously mentioned in the studies conducting during the COVID-19 pandemic [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. It was reported that the students were experiencing psychological issues related to panic, depression, stress, anger, anxiety, sadness, fear confusion, as well as social dysfunction during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…As a result of the increase in the time spend on social media, the students have become more exposed to read, heard, or see news related to the COVID-19 and therefore they were psychologically affected. Similar findings were previously mentioned in the studies conducting during the COVID-19 pandemic [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. It was reported that the students were experiencing psychological issues related to panic, depression, stress, anger, anxiety, sadness, fear confusion, as well as social dysfunction during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…According to one systematic review of the impact of the COVID-19 pandemic on the mental well-being of people, it can be concluded that many segments of the population have experienced a negative impact on their mental state. A study conducted among the Iranian population showed that medical students had significantly higher scores for stress, anxiety, and depression compared with that of medical staff and community populations [4]. Fear of a new virus, social distancing, job loss, and increased media attention, along with a lack of information and knowledge about the pandemic, has created and exacerbated feelings of insecurity, depression, and anxiety [5].…”
Section: Introductionmentioning
confidence: 99%
“…The current pandemic of novel coronavirus disease (COVID-19) is spreading and affecting people exponentially day after day. Novel diseases are traumatic as they give a sense of uncertainty and act as a threat to life which triggers fear of illness (Vahedian-Azimi, 2020). Extant literature reveals negative mental health outcomes are sequelae of exposure to traumatic events (Pine et al, 2005;Su & Chen, 2015).…”
Section: Introductionmentioning
confidence: 99%